2021
DOI: 10.3389/fmicb.2021.741093
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Epidemiological Characteristics and Molecular Features of blaKPC–2- or blaNDM–1-Positive Klebsiella pneumoniae Isolates in a Newly Established Hospital

Abstract: The emergence of hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) was regarded as an emerging threat in clinical settings. Here, we investigated the prevalence of CRKP strains among inpatients in a new hospital over 1 year since its inception with various techniques, and carried out a WGS-based phylogenetic study to dissect the genomic background of these isolates. The genomes of three representative blaNDM–1-positive strains and the plasmids of four blaKPC–2-positive strains were selected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…In this study, bla NDM -harbouring IncX3-type plasmids were the most common plasmids among all carbapenemase-encoding plasmids. The IncX3-type plasmid was self-transmissible, which has been confirmed in this study and previous reports [ 18 , 19 ]. Furthermore, the same IncX3-type plasmid was detected in E. xiangfangensis strains belonging to different clones.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, bla NDM -harbouring IncX3-type plasmids were the most common plasmids among all carbapenemase-encoding plasmids. The IncX3-type plasmid was self-transmissible, which has been confirmed in this study and previous reports [ 18 , 19 ]. Furthermore, the same IncX3-type plasmid was detected in E. xiangfangensis strains belonging to different clones.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, many studies characterized the genetic environments of bla KPC-2 and various mobile genetic elements played a critical role in the rapid spread of bla KPC-2 [ 35 , 36 ]. In this study, we found that the genetic environments of bla KPC−2 shared the core structure with IS Kpn27 - bla KPC−2 -IS Kpn6 , which was similar to the previous study [ 37 ]. Bacteria could acquire preexisting resistance determinants to promote drug resistance, which was achieved through the concerted activities of mobile genetic elements (such as IS, transposons) and plasmids and integrative conjugative elements [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…imipenem, meropenem and doripenem) have become the last line of defense in the treatment of K. pneumoniae infections [ 3 ]. Unfortunately, due to the spread of mobile genetic elements has led to a steady increasing in CRKP [ 4 ]. The World Health Organisation (WHO) issued a report in 2017 highlighting the serious threat posed by carbapenem-resistant K. pneumoniae (CRKP) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%